In vivo site-specific recombination using the β-rec/six system. (July 2008) - Servert, Pilar; Díaz, Vicente; Lucas, Daniel; de la Cueva, Teresa; Rodriguez, Maria C.; García-Castro, Javier; Alonso, Juan C.; Martínez-A, Carlos; González, Manuel A.; Bernad, Antonio
The prokaryotic β serine recombinase (β-rec) catalyzes site-specific recombination between two directly oriented six sites (93 bp) in mammalian cells, both in episomal and in chromosomally integrated substrates. The β-rec/six exclusive intramolecular site-specific recombination (SSR) system has been proposed as a suitable approach when several independently controlled recombination events are needed in a single cell. Here we explored the use of the β-rec/six system for selective induction of genome-targeted modifications. We generated and analyzed mouse transgenic lines (Tgβ) expressing β-rec under the control of the Lck promoter. β-rec activity was demonstrated, and there was no evidence of alterations to thymic or peripheral T cell development. We developed two transgenic mouse lines harboring different target sequences (Tgrec and KOsix) and analyzed the effect of β-rec expression on these animals. The results indicate that the β-rec/six SSR system is functional for in vivo gene-targeting applications.